Efeitos do exercício físico e laser de baixa intensidade sobre a articulação do joelho de ratos Wistar submetidos a um modelo de artrite reumatoide - Neves, Morgana (2020)
Rheumatoid arthritis presents an inflammatory profile that manifests in acute and chronic phases. As a consequence the individual presents pain and functional disability. Thus, the search for treatments that modulate the inflammatory process and maintain and/or improve peripheral functionality both in the early and late stages of the disease becomes pertinent. The objective of the study was to investigate whether treatment with low level laser therapy (LLLT) and physical exercise modulate the inflammatory process, to evaluate whether the treatments reflect on the return of functionality, and whether they reduce the deleterious effects of joint tissue. In the study the sample consisted of 128 male Wistar rats. They were divided into two periods of the disease: acute and chronic with 64 animals in each group. The animals were submitted to an experimental rheumatoid arthritis protocol with two Freund Complete Adjuvant (CFA) inoculations. All animals were evaluated (acute 4 evaluations and chronic 8 evaluations) for joint disability by paw elevation time (PTE), joint edema, and nociceptive threshold. As a treatment protocol, we opted for LLLT and stair climbing resistance exercise. After euthanasia, a total leukocyte count, percentage of cells, and the knee joints dissected, decalcified and included in paraffin to obtain the histological slides were performed. For cell differentiation analyses, the parametric ANOVA test was used as a criterion, with post-T test (LSD), functional analysis of factor ANOVA, and morphometry Generalized models with post-Sidak test. During the evaluations, the animals treated in the acute and chronic group decreased PTE and edema, and increased the nociceptive threshold. For acute and chronic cell differentiation, the treated animals reduced the amount of inflammatory cells compared to untreated injury group. In the morphological aspects, the animals of the lesion + treatment groups presented tissue alterations compared to the control group, and the groups treated with an association of treatments improved the tissue aspects evaluated for the joint cartilage, synovial membrane, and periosteum in both the acute and chronic periods of the disease. In morphometric analysis, it was found that the combination of treatments showed better effects when in isolation. The experimental arthritis induction model was effective in reflecting the deleterious effects of tissue on the knee joint, the combination of LLLT and exercise are effective in reducing the inflammatory and functional parameters analyzed.